Strength field tests performance are correlated with isokinetic strength of shoulder rotator muscles in female handball players - dos Santos Andrade, M.; Fachina, R. J.; Cruz, W.; Benedito-Silva, A. A.; da Silva, A. C.; De Lira, C. A. (The Journal of Sports Medicine and Physical Fitness, 2014)
BACKGROUND: The aim of this study was to analyze the relationship between the isokinetic shoulder strength of the athletes and their performance on strength field tests. Data on the balance and functional strength ratios of the internal and external rotator muscles of shoulders of handball players was also investigated.